Linear Equations - Exercise 1

Justify each step below where the equation  x/3 + 3(x + 5) = 4x - 1 is solved with solution  x = 24.

STATEMENT JUSTIFICATION
x/3 + 3(x + 5) = 4x - 1

x/3 + 3x + 15 = 4x - 1

3(x/3 + 3x + 15) = 3(4x - 1)

x + 9x + 45 = 12x - 3

10x + 45 = 12x - 3

48 = 2x

24 = x

 

Given

___________________________________

___________________________________

___________________________________

___________________________________

___________________________________

___________________________________

 

 

Linear Equations - Exercise 2

Solve the linear equation  5x + 3(x + 1) = 2x/5 - 1 and give the justification for each step as was done in Exercise 1.

STATEMENT JUSTIFICATION
5x + 3(x + 1) = 2x/5 - 1

___________________________________

___________________________________

___________________________________

___________________________________

___________________________________

___________________________________

 

 

 

Given

___________________________________

___________________________________

___________________________________

___________________________________

___________________________________

___________________________________